High Resolution Infrared Spectroscopy in Astronomy: Proceedings of an ESO Workshop Held at Garching, Germany, 18-21 November 2003 - Käufl, Hans Ulrich; Moorwood, Alan F. M.; Siebenmorgen, Ralf (ESO Astrophysics Symposia, 2005)
Alan F. M. Moorwood